Evaluation of Online Learning Systems on Vocational Education in the COVID-19 Pandemic - M. Nilzam Aly; Nur Hamid; Elvara Norma Aroyandini; Nor Kholis; Septyani Prihatiningsih; Rizky Amalia Sinulingga (AL-ISHLAH: Jurnal Pendidikan, 2022)
Some online learning methods are experiencing very fast dynamics these days. The dynamics that are developing are a form of adjustment to the needs of lecturers and students when the Covid-19 pandemic is severe. Airlangga University's online learning system e-Learning Application (AULA) has tried to be maximized to face the current dynamics of change. This study aims to evaluate online learning in theoretical and practical classes. The evaluation is seen from the perceptions of students from the Vocational Faculty. This evaluation is used to analyze three main aspects of the use of AULA, namely delivery, interactive, and assessment in the implementation of theoretical and practicum courses. This evaluation research uses a quantitative approach with the main data collection being a questionnaire. In addition, in-depth interviews were also conducted to confirm the questionnaire. The results of the analysis of this study indicate that the perceptions of students tend to be dissatisfied with the use of AULA in the practical class. Almost all sections in the interactive and assessment aspects have a fairly low score. The findings in this study indicate that the implementation of online practicum classes is still not able to accommodate students' interests related to the full mastery of skills from practicum classes. Although, the combination of vocational education and training with E-learning during a pandemic is considered the only logical choice. This is because learning objectives can only be achieved using this method compared to having to face to face during the Covid-19 pandemic.